Engagement y autoeficacia en estudiantes de la carrera de Pedagogía de las Artes y Humanidades - Sampedro Chicaiza, Kerly Damaris (2025)
The present research analyzed the relationship between academic engagement and selfefficacy among second- and seventh-semester students in the Pedagogía de las Artes y Humanidades major at the Universidad Nacional de Chimborazo. Academic engagement involves students' emotional, cognitive, and behavioral participation in academic activities, as reflected in dedication, absorption, and vigor. Self-efficacy is the belief in one's ability to handle challenges. This study uses a quantitative, non-experimental, correlational, cross-sectional, and field-based design. The population comprised students from the relevant degree, and the non-probabilistic purposive sample included 48 secondand seventh-semester students. Data were collected using psychometric techniques, specifically the UWES-S17 and the General Self-Efficacy Scale. Results showed average engagement and self-efficacy. Dedication was strongest; vigor was weakest, especially for seventh-semester students. A significant correlation appeared in the seventh semester, but not in the second. This research opens new lines of inquiry for forming future teachers.